PRODUCTION PERFORMANCE AND FINANCIAL ANALYSIS OF GLASS EEL (Anguilla bicolor) NURSERY AT DIFFERENT STOCKING DENSITIES USING RAS - Aslia, Aslia; Budiardi, Tatag; Hadiroseyani, Yani; Diatin, Iis (Indonesian Aquaculture Journal, 2025)
Eel aquaculture remains dependent on wild-caught glass eels, whose supply fluctuates seasonally and peaks during the rainy season. Improving nursery efficiency through optimized stocking density is therefore essential. This study evaluated the effects of three stocking densities (1, 2, and 3 g L-¹) on the production performance and financial feasibility of glass eel (Anguilla spp.) nursery operations in recirculating aquaculture systems (RAS). Stocking density significantly affected survival, biomass yield, and profitability (p < 0.05). The highest density (3 g L-¹) resulted in the lowest survival rate (35.69 ± 3.70%), which was significantly lower than both 1 g L-1 and 2 g L-¹, yet produced the greatest biomass (11.42 ± 0.57 g L-¹). Financial analysis showed that all treatments were viable, with 3 g L-¹ yielding the highest profit (IDR 378,035,622 ± 45,089,672). Despite reduced survival, profitability remained relatively stable across treatments, indicating that biomass gain compensated for mortality-related losses. These findings demonstrate that a stocking density of 3 g L-1 provides the most advantageous balance between production output and economic return for glass eel nursery operations in RAS.